2016
DOI: 10.1155/2016/7987081
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Polyarteritis Nodosa Associated with Vertebral Artery Vasculitis Treated Successfully with Tocilizumab and Cyclophosphamide

Abstract: Pediatric polyarteritis nodosa is rare systemic necrotizing arteritis involving small- and medium-sized muscular arteries characterized by aneurysmal dilatations involving the vessel wall. Aneurysms associated with polyarteritis nodosa are common in visceral arteries; however intracranial aneurysms have also been reported and can be associated with central nervous system symptoms, significant morbidity, and mortality. To our knowledge extracranial involvement of the vertebral arteries has not been reported but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Case reports have shown TCZ to be effective for a variety of other diseases, including autoimmune hemolytic anemia [ 171 , 172 ], reactive arthritis [ 173 ], autoimmune encephalitis [ 174 , 175 ], myasthenia gravis [ 176 ], Blau syndrome [ 177 ], anti-Caspre2 syndrome [ 178 ], refractory organizing pneumonia associated with Sjögren’s syndrome [ 179 ], cancer-related cachexia [ 180 ] and steroid refractory immune-mediated adverse events secondary to immune check point inhibitors [ 181 ]. Besides large vessel vasculitis, several case reports have indicated that TCZ has effects on rheumatoid vasculitis [ 182 ], polyarteritis nodosa [ 183 , 184 ], microscopic polyangiitis [ 185 , 186 ] and cryoglobulinemia vasculitis [ 187 ]. A report showed that epidural administration of TCZ reduced pain due to sciatica with lumbar spinal stenosis [ 188 ].…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%
“…Case reports have shown TCZ to be effective for a variety of other diseases, including autoimmune hemolytic anemia [ 171 , 172 ], reactive arthritis [ 173 ], autoimmune encephalitis [ 174 , 175 ], myasthenia gravis [ 176 ], Blau syndrome [ 177 ], anti-Caspre2 syndrome [ 178 ], refractory organizing pneumonia associated with Sjögren’s syndrome [ 179 ], cancer-related cachexia [ 180 ] and steroid refractory immune-mediated adverse events secondary to immune check point inhibitors [ 181 ]. Besides large vessel vasculitis, several case reports have indicated that TCZ has effects on rheumatoid vasculitis [ 182 ], polyarteritis nodosa [ 183 , 184 ], microscopic polyangiitis [ 185 , 186 ] and cryoglobulinemia vasculitis [ 187 ]. A report showed that epidural administration of TCZ reduced pain due to sciatica with lumbar spinal stenosis [ 188 ].…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%
“…4 Delayed or no treatment in PAN, may lead to significant morbidity and mortality. 6 In our case, he is continuously on treatment and follow-up since childhood. Corticosteroids are mainstay of treatment on PAN.…”
mentioning
confidence: 67%
“…Few cases were treated with etanercept [65][66][67], one with infliximab [68], tocilizumab [69], adalimumab [70] and lastly, a case treated with rituximab [71]. All cases showed a good response to treatment with achieved remission upon clinical and biochemical basis without serious side effects.…”
Section: Polyarteritis Nodosamentioning
confidence: 99%